Exploring Private School Teachers' Perceptions of Professional Development Sessions Through the Lens of Active Experimentation - Ockerman, Lisa S.; Bagui, Sikha (International Journal of Changes in Education, 2024)
The goal of this research study was to investigate the effects of D.A. Kolb’s active experimentation stage of experiential learning theory (ELT) on teacher professional development. This qualitative interpretive phenomenological study addressed the problem of teachers’ desires for effective professional learning experiences to improve student learning and instruction in the classroom. The research questions explored the perceptions of private school teachers regarding professional development sessions, specifically in the context of active experimentation. The study aimed to investigate the advantages of promoting a professional culture of continuous learning and teamwork among teachers through various methods such as lab classrooms, peer observation, professional learning communities, and peer coaching. The study adopts a descriptive approach utilizing focus group discussion and semi-structured interviews for data collection. Purposeful sampling was used to determine the sample and criterion sampling was used to select the participants. Biographic data was collected to provide background information about the participants involved. The biographic data allowed for stratification enabling the examination of various factors connected to the aim of the study. The study focused on understanding the benefits of providing teacher support through active experimentation during professional development sessions. Results showed that although teachers did not explicitly reference ELT when discussing effective strategies during professional development sessions, they referenced the value of hands-on, active participation in real-classroom stimulations during teacher professional development. The study’s findings also indicate a need for creating a consistent framework for professional development sessions that includes active learning, teacher collaboration, and continuous support in a culture anchored in trust. Received: 29 November 2023 | Revised: 27 December 2023 | Accepted: 31 December 2023 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study.